ISOLATION OF SILVER NANOPARTICLES USING THE GREEN SYNTHESIS METHOD IN CELL CULTURE AND STUDY OF THEIR ANTICARCINOGENIC EFFECT (Global Conference on Multidisciplinary Research and Innovation, 2026)
In this study, it was aimed to isolate silver nanoparticles using the green synthesis method and to investigate their properties and anticarcinogenic effects. This work contributes, on the one hand, to the development of environmentally safe and efficient nanotechnologies and, on the other hand, to the production of new biologically active substances supporting oncological diseases and the immune system. In this study, silver nanoparticles (AgNPs) obtained through green synthesis using various parts of plants possess great potential for application in medicine and industry. A promising but insufficiently studied direction is the use of Codonopsis clematidea in the synthesis of silver nanoparticles. The study is devoted to the development of a method for obtaining silver nanoparticles through green synthesis using different parts of Codonopsis clematidea (flowers, leaves, bark) and to the investigation of the properties of the resulting product.
Keywords: Codonopsis clematidea, green synthesis, silver nanoparticles, anticarcinogenic effect, bottom-up approach.